2021
DOI: 10.3390/molecules26123698
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Atmospheric-Pressure Plasma Treatments on Fracture Toughness of Carbon Fibers-Reinforced Composites

Abstract: In this study, nano-scale fillers are added to epoxy matrix-based carbon fibers-reinforced composites (CFRPs) to improve the mechanical properties of multi-scale composites. Single-walled carbon nanotubes (SWCNTs) used as nano-scale fillers are treated with atmospheric-pressure plasma to introduce oxygen functional groups on the fillers’ surface to increase the surface free energy and polar component, which relates to the mechanical properties of multi-scale composites. In addition, the effect of dispersibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
3
3
0
Order By: Relevance
“…Here, all the DGEBA/PEI blends exhibit excellent linear relationships between the K IC and the G IC . Thus, we confirmed that the PEI particles in the epoxy matrix act as stress concentrators to absorb the external energy and mitigate the crack growth [41][42][43][44][45][46]. 7a,d, neat DGEBA displayed a regular fracture surface, which is the typical characteristic of a brittle fracture.…”
Section: Mechanical Properties Of the Dgeba/pei Blendssupporting
confidence: 70%
See 1 more Smart Citation
“…Here, all the DGEBA/PEI blends exhibit excellent linear relationships between the K IC and the G IC . Thus, we confirmed that the PEI particles in the epoxy matrix act as stress concentrators to absorb the external energy and mitigate the crack growth [41][42][43][44][45][46]. 7a,d, neat DGEBA displayed a regular fracture surface, which is the typical characteristic of a brittle fracture.…”
Section: Mechanical Properties Of the Dgeba/pei Blendssupporting
confidence: 70%
“…The mechanical properties, including the K IC and G IC , of the DGEBA/PEI blends are indicated in Figure 6 d. Here, all the DGEBA/PEI blends exhibit excellent linear relationships between the K IC and the G IC . Thus, we confirmed that the PEI particles in the epoxy matrix act as stress concentrators to absorb the external energy and mitigate the crack growth [ 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: 3 Mechanical Properties Of the Dgeba/pei Blendssupporting
confidence: 65%
“…Moreover, the diffraction patterns of the PBNNS-1 and PBNNS-7 are similar to that of the pristine BNNS, each exhibiting a diffraction peak at 2 θ = 45° due to the (100) crystal plane, thereby indicating that these three samples have the same characteristic crystalline structures. However, the XRD pattern of the PBNNS-10 is different from that of the pristine PBNNS, PBNNS-1, and PBNNS-7 samples, thus confirming that the crystalline structure of BNNS is destroyed by excessive plasma-treatment (i.e., more than 10 min), as has been observed previously [ 45 , 46 , 47 ].…”
Section: Resultssupporting
confidence: 78%
“…The deconvoluted XPS C 1s curves of the CF in Figure a possess three peaks of C–C, C–N/C–O, and OC–O with a content of 46.82, 47.35, and 5.83% at 284.8, 285.8, and 290.3 eV, respectively . In Figure b–d, the OC–O unit vanishes, but the CO functionality appears at 286.4–286.7 eV after surface coating, which mainly results from the quinone monomer provided by PDA. In Figure b–d, CF-hybrid30 has the highest active carbon content of up to 74.62% (the sum of C–N/C–O and CO units), which echoes the peak sum of O and N contents (22.25%) in Table .…”
Section: Resultsmentioning
confidence: 95%